A systemic assessment of the environmental impacts and remediation strategies for chloroacetanilide herbicides. (October 2019) - Mohanty, Satya Sundar; Jena, Hara Mohan
Abstract: Chloroacetanilide class of herbicides such as acetochlor, alachlor and butachlor, widely used for the control of unwanted grasses and weeds in various crop cultivations, are classified as B2, L2 and C classes of carcinogens by various environmental agencies. Extensive and uncontrolled usage of these herbicides create imbalance in the environment and so fate of these compounds become a subject of concern. In this review, an attempt has been made to summarize the toxicological aspects, and critically analyse the available remediation technologies of these herbicides. The review proposes that biological methods in the presence of additional carbon sources have a better probability for the complete mineralization of these herbicides. Application of the bacterial strain Paracoccus sp. has emerged as the most advantageous, and sustainable remediation technology due to its wide spectrum of substrate specificity. The bacterial strain is able to degrade 100 mg/l of various chloroacetanilide herbicides within a span of 5 days. Among the physicochemical treatment technologies, application of ozone for the treatment of the herbicides was found to be highly efficient. However, production of ozone resistant by-products reduces its efficiency for subsequent use. The review also hints on the potential research gap and the need of precision required for the studies in the areas of integrated treatment technologies, fate of degradation residues and intermediate metabolites, etc. for better understanding of their fate and to achieve complete removal from the environment.